Pengaruh Peran Digitalisasi Dan Service Excellent Terhadap Optimalisasi Program Kawasan Lingkungan Sadar Akan Administrasi Kependudukan (KALIMASADA) Di Kelurahan Dukuh Sutorejo Kota Surabaya - M. Khoirur Rifqi; Maharani Ikaningtiyas (Jurnal Akuntan Publik, 2023)
This study aims to determine the effect of digitalization and excellent service on the optimization of the Population Administration Awareness Environmental Area (KALIMASADA) program in Dukuh Sutorejo Village. This study used a survey method by distributing questionnaires and questionnaires with a sample of Dukuh Sutorejo Village residents who entered Kalimasada data (residents whose population administration was incomplete) aged 18-64 years. The number of samples in the study was obtained by multiplying the number of variable indicators used by the minimum number, namely 5. The sampling technique was carried out using the Accidental Sampling technique, namely a sampling technique based on chance, that is, anyone who accidentally meets a researcher can be used as a sample if seen by others. that happen to be encountered is suitable as a data source. The data used in this research is primary data by distributing questionnaires. The results of this study indicate that digitalization and excellent service partially and simultaneously have a positive effect on optimizing the Population Administration Awareness Environmental Area (KALIMASADA) program in Dukuh Sutorejo Village.